2013
DOI: 10.1037/a0028261
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements to audiovisual scenes reveal expectations of a just world.

Abstract: When confronted with bad things happening to good people, observers often engage reactive strategies, such as victim derogation, to maintain a belief in a just world. Although such reasoning is usually made retrospectively, we investigated the extent to which knowledge of another person's good or bad behavior can also bias people's online expectations for subsequent good or bad outcomes. Using a fully-crossed design, participants listened to auditory scenarios that varied in terms of whether the characters eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 28 publications
4
39
0
1
Order By: Relevance
“…Before revealing what happened next, participants were given a preview of two possible outcomes for the protagonists: a good one (e.g., a successful business contract) and a bad one (e.g., a terrible car accident). People's eye gaze revealed that they were expecting good outcomes to befall good protagonists and bad outcomes to befall bad protagonists [8]. When individuals view a morally good or bad actor, their visual attention reflects expectations that people will get what they deserve.…”
Section: Moral Concerns Tune and Are Tuned By Attentionmentioning
confidence: 98%
“…Before revealing what happened next, participants were given a preview of two possible outcomes for the protagonists: a good one (e.g., a successful business contract) and a bad one (e.g., a terrible car accident). People's eye gaze revealed that they were expecting good outcomes to befall good protagonists and bad outcomes to befall bad protagonists [8]. When individuals view a morally good or bad actor, their visual attention reflects expectations that people will get what they deserve.…”
Section: Moral Concerns Tune and Are Tuned By Attentionmentioning
confidence: 98%
“…Research has confirmed that observers judge bad (good) people as deserving of their fortuitous bad (good) fortunes (e.g., Callan, Sutton, Harvey, & Dawtry, 2014; Pepitone & L’Armand, 1996; Rice & Trafimow, 2011), and the innocent suffering of devalued (vs. valued) individuals and groups as less unfair (e.g., Callan, Dawtry, & Olson, 2012; Callan, Powell, & Ellard, 2007; Correia, Vala, & Aguiar, 2007; Lerner & Agar, 1972). Crucially, people also expect bad (good) things to happen to bad (good) people (e.g., Callan, Ferguson, & Bindemann, 2013; Kaplowitz, 1979). For example, Callan, Ellard, and Nicol (2006) found that participants rated a man who cheated on his wife as more deserving of a completely unrelated car accident than participants who learned the man did not cheat.…”
mentioning
confidence: 99%
“…From this perspective, initial, schema-based reactions to injustice may lead people to, for example, intuitively connect a random bad outcome to the recipient's prior bad deeds , have the impulse to punish perpetrators of harm (Goldberg, J. S. Lerner, & Tetlock, 1999), or spontaneously help a victim (Holmes, Miller, & Lerner, 2002;Rand, Greene, & Nowak, 2012). In support, a growing body of experimental research has suggested that people's reactions to victimization may occur intuitively-that is, without requiring a rational mind-set or much effortful thought (e.g., Aguiar, Vala, Correia, & Pereira, 2008;Callan, Ferguson, & Bindemann, 2013;Callan, Sutton, & Dovale, 2010;Goldberg et al, 1999;Loseman & van den Bos, 2012;Maas & van den Bos, 2009;van Prooijen & van de Veer, 2010). For example, adopting an eye-tracking methodology, Callan et al (2013) found that the good (bad) behavior of characters within audio-visual scenes biased participants' eye gaze towards images of good (bad) outcomes before the actual outcomes were revealed verbally.…”
Section: How Much Does Effortful Thinking Underlie Observers' Reactiomentioning
confidence: 79%
“…In support, a growing body of experimental research has suggested that people's reactions to victimization may occur intuitively-that is, without requiring a rational mind-set or much effortful thought (e.g., Aguiar, Vala, Correia, & Pereira, 2008;Callan, Ferguson, & Bindemann, 2013;Callan, Sutton, & Dovale, 2010;Goldberg et al, 1999;Loseman & van den Bos, 2012;Maas & van den Bos, 2009;van Prooijen & van de Veer, 2010). For example, adopting an eye-tracking methodology, Callan et al (2013) found that the good (bad) behavior of characters within audio-visual scenes biased participants' eye gaze towards images of good (bad) outcomes before the actual outcomes were revealed verbally. This finding highlights how a concern for justice establishes an automatic preference for observers to expect outcomes that are consistent with what people deserve.…”
Section: How Much Does Effortful Thinking Underlie Observers' Reactiomentioning
confidence: 99%
See 1 more Smart Citation